2006
DOI: 10.2516/ogst:2006019
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Au-Pd and Ag-Pd Clusters Synthesised by $\gamma $ or Electron Beam Radiolysis and Study of the Reactivity/Structure Relationships in the Selective Hydrogenation of Buta-1,3-Diene

Abstract: Résumé -Agrégats bimétalliques Au-Pd et Ag-Pd synthétisés par réduction radiolytique : étude des relations réactivité/structure en hydrogénation sélective du buta-1,3-diène -Des catalyseurs Ag-Pd et Au-Pd (sous forme d'alliage ou de structure coeur-coquille) ont été synthétisés par réduction radiolytique (rayons gamma ou faisceau d'électrons). L'étude de l'hydrogénation sélective de buta-1,3-diène par ces différents nanoagrégats déposés sur alumine a permis de déterminer les effets de la composition et de la s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 21 publications
1
37
1
Order By: Relevance
“…The scale bar in conventional TEM images is irradiation such as g-ray irradiation (40 Gy/min). This trend is quite similar to the results for the irradiation-synthesized Au-Pt, Au-Pd systems, which have been reported by (Remita et al, 2003(Remita et al, , 2005Redjala et al, 2006). In case of low dose rate irradiation, as the reduction rate is very small, the growth of nanoparticles tends to occur easily.…”
Section: Tem and Stem Observationssupporting
confidence: 88%
See 1 more Smart Citation
“…The scale bar in conventional TEM images is irradiation such as g-ray irradiation (40 Gy/min). This trend is quite similar to the results for the irradiation-synthesized Au-Pt, Au-Pd systems, which have been reported by (Remita et al, 2003(Remita et al, , 2005Redjala et al, 2006). In case of low dose rate irradiation, as the reduction rate is very small, the growth of nanoparticles tends to occur easily.…”
Section: Tem and Stem Observationssupporting
confidence: 88%
“…Through the transmission electron microscope (TEM) observation and ultraviolet-visible (UV-vis) measurements, Remita et al (2003Remita et al ( , 2005 have already reported the synthesis of bimetallic nanoparticles such as Au-Pt, Au-Pd, and so on in various kinds of irradiation fields. They have concluded that the dose rate is an important factor to control the particle size and structures (Remita et al, 2003(Remita et al, , 2005Redjala et al, 2006). To study the dose rate effect on the size and structure of irradiationsynthesized nanoparticles more clearly, we made annular darkfield scanning transmission electron microscopy (ADF-STEM) observations with energy-dispersive X-ray spectroscopy (EDS) measurements for Au-Pd nanoparticles synthesized for various kinds of irradiation as well as conventional transmission electron microscope observations and ultraviolet-visible measurements.…”
Section: Introductionmentioning
confidence: 99%
“…With the Ag-promoted catalysts, C 1 and C 5 + selectivities were slightly improved at all loadings [28]. Thus, the presence of a weakly hydrogenating metal [29], Ag, did not adversely affect selectivity to a significant degree, even when excessive amounts of promoter were added [28].…”
Section: Example #4-impact Of Loading For Pt and Ag Promoted Catalystsmentioning
confidence: 89%
“…Au-Pd nanoparticles were produced by radiolysis, then adsorbed on an alumina support [98]. The aqueous solution containing HAuCl 4 and Pd(NO 3 ) 2 was irradiated under a N 2 atmosphere in the presence of PVA as stabilizing agent and of 2-propanol as scavenger of oxidizing OH‚ radicals.…”
Section: Radiolysis-assisted Reductionmentioning
confidence: 99%